Pengaruh Literasi Keuangan Terhadap Manajemen Keuangan Pribadi Mahasiswa Program Studi Akuntansi Di Universitas Cipasung Tasikmalaya - Ridwan, Rizky; Lestari, Dheri Febiyani; Rachmanda, Yudi Setia; Nurlaila, Fitri (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine the effect of financial literacy on accounting students' personal financial management. Chen & Volpe, (1998) states that financial literacy is defined as the ability to manage finances so that life can be more prosperous in the future. In this case, it is not only knowledge about managing finances, but also the behavior of each individual student in increasing financial literacy. The sample of this research was 187 Accounting Students with data collection using a questionnaire. The results showed that financial literacy has an effect on personal financial management of accounting students with a significance value of t of 0.000 <0.05, which is significant or H0 is rejected, meaning that there is a significant relationship between financial literacy and personal financial management of accounting students. The results of the research correlations between the independent variable and the dependent variable R are known to be 0,697 this number shows the level of correlation or relationship between the two variables is at the interpretation of 0.50 - 07.0 with a strong correlation with a Coefficient of Determination of 48,6% and the rest are other variables that are not the focus of research This. Keywords: Financial Literacy, Personal Financial Management.